2005
DOI: 10.1093/tropej/fmi071
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness: An Index for Subclinical Atherosclerosis in Type 1 Diabetes

Abstract: Cardiovascular disease and the development of coronary artery atherosclerosis play a pivotal role in increasing mortality in patients with diabetes. The aim of the present study was to determine the presence of subclinical atherosclerosis (measured as carotid intima-media thickness [cIMT] and to study possible associated risk factors in adolescents with type 1 diabetes. Forty type 1 diabetic subjects, aged 11-30 years, with duration of diabetes 3-25 years and 40 normal healthy controls, were included. Blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
6
22
1
Order By: Relevance
“…In spite of that, the difference found in the mean cIMT between control subjects and diabetic patients in our study was lower than that reported by Järvisalo et al (0.02 vs. 0.05 mm), despite the similar age and mean diabetes duration of the study samples. Other authors have reported differences in mean cIMT above or below the difference reported here; differences between case and control subjects vary from 0.01 mm (20) to 0.20 mm (13).…”
Section: Intima-media Thickness In Type 1 Diabetescontrasting
confidence: 49%
See 1 more Smart Citation
“…In spite of that, the difference found in the mean cIMT between control subjects and diabetic patients in our study was lower than that reported by Järvisalo et al (0.02 vs. 0.05 mm), despite the similar age and mean diabetes duration of the study samples. Other authors have reported differences in mean cIMT above or below the difference reported here; differences between case and control subjects vary from 0.01 mm (20) to 0.20 mm (13).…”
Section: Intima-media Thickness In Type 1 Diabetescontrasting
confidence: 49%
“…However, its ability to predict CHD in pediatric patients has been fairly explored (13,14). Data in pediatric populations are scant, and no publications currently exist in Hispanic patients.…”
mentioning
confidence: 99%
“…[1][2][3][4] Pediatric patients with a history of cardiac transplantation, thoracic radiation therapy, and specific syndromes and systemic diseases are also at increased risk for coronary artery disease at a young age. [5][6][7][8] Catheter-based angiography is the historical standard for coronary artery evaluation. A noninvasive alternative such as coronary computed tomography angiography (CTA) was previously limited because of elevated heart rates that could compromise coronary CTA scan quality and increased sensitivity to radiation which is a special concern in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…17 An Asian study also reveals association of age, duration of diabetes, both systolic and diastolic blood pressures and HDL levels with carotid intima-media thickness in patients with type 2 diabetes mellitus. 18 Glycemic control as represented by HbA1c in type 1 diabetes patients showed a significant relationship with CIMT only in female patients and not in male patients. 19 Our study did not show any association of glycemic control with CIMT.…”
Section: Discussionmentioning
confidence: 88%